An Implicit Enumeration Algorithm to Generate Tests for Combinational Logic Circuits - Goel (IEEE transactions on computers, 1981)
The D-algorithm (DALG) is shown to be ineffective for the class of combinational logic circuits that is used to implement error correction and translation (ECAT) functions. PODEM (path-oriented decision making) is a new test generation algorithm for combinational logic circuits. PODEM uses an implicit enumeration approach analogous to that used for solving 0-1 integer programming problems. It is shown that PODEM is very efficient for ECAT circuits and is significantly more efficient than DALG over the general spectrum of combinational logic circuits. A distinctive feature of PODEM is its simplicity when compared to the D-algorithm. PODEM is a complete algorithm in that it will generate a test if one exists. Heuristics are used to achieve an efficient implicit search of the space of all possible primary input patterns until either a test is found or the space is exhausted.